Nutraceutical properties of goat milk than cow milk - Meena, Priyanka; Pandey, Anurag; Raut, Subhash; Raman, Ravi (Indian Farming, 2018)
Goat milk is a rich source of more bioavailable proteins, fats, vitamins and minerals with great suitability for infant foods in comparison to cow milk. Due to its high nutritive value and physiological properties, goat milk should be promoted in the developing countries like India where malnutrition and diseases are more prevalent along with high poverty levels. The maintenance cost, general management and feeding of the dairy goat are very low. But commercialization and utilization of goat milk are still lacking in developing countries.